Dispersion and their tribological properties of molybdenum nanoparticles with different particle sizes as additive in lubricating oil - Tianhua Chen (Functional Materials, 2018)
Using silane coupling agent KH-570 as the surface modifier-molybdenum nanoparticles with various particle sizes were prepared by mechanical ball milling method. The molybdenum nanoparticles with different particle sizes were added into 900SN base oil to form the experimental lubricating oils. The dispersion of molybdenum nanoparticles in the lubricating oil was investigated by measuring the absorbance of the oil and the tribological properties of the molybdenum nanoparticles as the lubricating oil additive were studied by a reciprocating friction tester. The results show that the molybdenum nanoparticles have good dispersion in the lubricating oil due to steric effect of the surface modified nanoparticles. The nanoparticles with smaller size exhibit better dispersion Meanwhile the excellent lubricating effect of the molybdenum nanoparticles in the lubricating oil is observed because these nanoparticles fill in some micro-pits on the worn surface.The particle size is smaller the better the repairing effect is for the worn surface.When the particle size of the molybdenum nanoparticles is about 40 nm, the molybdenum nanoparticles are dispersed well in the experimental lubricating oil and the oil shows good antifriction and antiwear performance.